The Correlation between EFL Students’ Metacognitive Reading Strategy and their Reading Comprehension on English Expository Text - Nurul Fadhilah Gazali; Sultan Baa (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
The study aimed at revealing the correlation between English as a Foreign Language (EFL) students’ metacognive reading strategy and their reading comprehension on English expository text. The research applied quantitative method, particularly descriptive and correlational designs. The subjects were the students of Senior High School (SMAS) Buqátun Mubarakah Makassar. The instrument used to collect the data was questionnaire which was adapted from SORS inventory. The data were analyzed by using SPSS Version 22, particularly Pearson Product Moment Correlation Formula. The results of the study showed that the majority of the students in this current time were in possession of high metacognitive reading strategy. Furthermore, the metacognitive reading strategy profile of SMAS Buqátun Mubarakah students was problem solving strategy where the students used some actions and procedures while working directly with the text. Since metacognitive reading strategy included awareness and conscious willing of one or more strategies to monitor reading comprehension, there was tendency of metacognitive reading strategy influenced reading comprehension of the students. Therefore, based on the analysis result of this study, there was significant positive correlation between the EFL students’ metacognitive reading strategy and their reading comprehension on English expository text.